Development of Healthy Coping Intervention Framework for Childhood Trauma Among Malaysian Young Adults - Jesynthia Wong, Robert (Universiti Malaysia Sarawak, 2025)
Childhood trauma has enduring effects on young adults’ emotional well-being, coping patterns, and resilience. In Malaysia, culturally grounded and accessible trauma-informed interventions remain limited. This study examines coping mechanisms among Malaysian young adults with childhood trauma and develops a validated Healthy Coping Framework. Guided by the Transactional Model of Coping, Narrative Theory, and Resilience Theory, an explanatory sequential mixed-methods design was applied across three phases. Phase 1 involved a needs assessment with 205 survey responses and 10 interviews. Quantitative findings showed that individuals with higher trauma exposure reported significantly greater maladaptive coping. Qualitative thematic analysis generated ten themes—such as self-doubt, intergenerational trauma, emotional neglect, identity conflict, and cultural dissonance—highlighting the psychosocial complexity of trauma experiences. Integrated findings informed the construction of the Healthy Coping Framework. Phase 2 focused on developing the framework and psychoeducational module. Expert evaluation indicated strong content validity (S-CVI/Ave = 0.835), while a pilot study with 28 participants demonstrated high treatment fidelity (94.6%) and feasibility of implementation. Phase 3 implemented the final module across nine workshops involving 227 participants. Pre–post assessments showed statistically significant improvements in coping awareness, emotional regulation, and resilience, with a large effect size (Cohen’s d = 1.00). This study addresses a critical gap in Malaysian mental health research by providing an empirically supported, culturally responsive trauma-informed coping framework. It offers practical tools to enhance coping and resilience among young adults and holds potential for broader application in community, educational, and clinical settings.